Single and split nitrogen application on the forage yield, morphogenesis, chemical composition, and tissue nitrogen fractions of Cynodon nlemfuensis under mob grazing - Oscar Ivan Tuz Matos; Wagner Paris; Olmar Antônio Denardin Costa; Fabiana Luiza Matielo de Paula; Adalberto Luiz de Paula; Jefferson Felipe Cavazzana; Saimon de Souza e Souza; Luis Fernando Glasenapp de Menezes (Semina: Ciências Agrárias, 2022)
The aim of this study was to evaluate the forage production, nutritional value (including protein fractions), and morphogenic characteristics of African star grass on nitrogen fertilizer in a single application and split applications of two and four, under mob grazing. The study was conducted on a 1.5 ha area with well-established African star grass (Cynodon nlemfuensis). The area was divided into 18 paddocks of 400 m2. for three treatments and six replications that were assigned through a randomized block design. The treatments were: Nap1 =Single N application; Nap2= split into two N applications; and Nap4: split into four N applications. Fertilizer application was 200 kg ha-1 of N in topdressing. Pasture was monitored weekly by sward height. Grazing began when the forage reached between 25 and 30 cm in height and ceased at 10 cm. In almost all months evaluated, Nap1 recorded the highest forage production, daily accumulation rate and available forage mass. Some morphogenic characteristics changed between the fertilization strategies, particularly in the months with greater water availability. The chemical composition did not fluctuate between treatments. African star grass can be fertilized with a single application of nitrogen at 200 kg ha-1 to attain greater forage mass and proportion of leaves, without any changes to the chemical composition and nitrogen fractions. These components were modified by the vegetative phase of the forage.